Bdellovibrio and Like Organisms in Lake Geneva: An Unseen Elephant in the Room? - Ezzedine, Jade A.; Jacas, Louis; Desdevises, Yves; Jacquet, Stéphan (Frontiers in Microbiology, 2020)
When considering microbial biotic interactions, viruses as well as eukaryotic grazers are known to be important components of aquatic microbial food webs. It might be the same for bacterivorous bacteria but these groups have been comparatively less studied. This is typically the case of the Bdellovibrio and like organisms (BALOs), which are obligate bacterial predators of other bacteria. Recently, the abundance and distribution of three families of this functional group were investigated in perialpine lakes, revealing their presence and quantitative importance (Paix et al. 2019). Here, a more in-depth analysis is provided for Lake Geneva regarding the diversity of these bacterial predators at different seasons, sites and depths. We reveal a seasonal and spatial (vertical) pattern for BALOs, along with correlations with environmental factors such as total phosphorus, total nitrogen, temperature and chlorophyll-a. BALOs were found to be relatively diverse (especially Bdellevibrionaceae) and assigned to both known and unknown phylogenetic clusters. At last we found that most BALOs were positively correlated to other bacterial groups, mainly Gram-negative, and in particular Myxococcales (among which many are predators of other microbes). This study is the first shedding light on this potentially important bacterial killing group in a large and deep lake.